Preserving Sanad in the Digital Age: A Case Study of Virtual Talaqqī for Qirā'āt al-Qurʾān at Markaz Qiroat Indonesia - Minan, Muhammad Aufal; Mustaqim, Abdul (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study aims to examine innovations in fully online qirā’āt learning at Markaz Qiroat Indonesia (MQI) and to analyze the quality and authenticity of sanad transmission within digital-based qirā’āt instruction. Design/methodology/approach – This study employed a qualitative research method using a case-study approach, with data collected through in-depth interviews, participatory observation, and documentation to examine learning practices, pedagogical processes, and the transmission of sanad in online qirā’āt learning at MQI; the authenticity of the sanad was verified through expert validation involving certified muqriʾ and sanad holders, including the examination of ijāzah chains, the continuity (ittiṣāl) of transmission, and the fulfillment of tashḥīḥ requirements in virtual talaqqī, while data triangulation was employed to enhance the credibility and validity of the findings. Findings – The findings indicate that online qirā’āt learning at MQI, implemented through a virtual talaqqī method, has the potential to maintain the quality of recitation and support the continuity of sanad, as evidenced by expert validation, the assessment of transmission continuity (ittiṣāl), and the application of tashḥīḥ criteria in virtual learning sessions. The use of the talwīn Manẓūmah Syāṭibiyyah method, compiled by Ihsan Ufiq, is found to effectively support participants’ understanding of the Matan Syāṭibiyyah as the core text of qirā’āt al-sab‘. Additionally, the online format provides flexible access for participants from diverse geographical backgrounds, although challenges remain in the form of limited affective interaction due to participants’ time constraints. Research implications/limitations – This study implies that well-structured digital learning, supported by a comprehensive curriculum, a humanistic pedagogical approach, and a rigorous evaluation system, can overcome affective and interactional limitations in online religious instruction. However, as a single case study, the findings are limited in generalizability and may not fully represent other qirā’āt institutions or learning contexts. Originality/value – This study contributes original insights into the integration of digital technology with traditional qirā’āt pedagogy.